The Incidence and Prevalence of Common Variable Immunodeficiency Disease in Taiwan, A Population-Based Study. - Chih-Wei Tseng; Kuo-Lung Lai; Der-Yuan Chen; Ching-Heng Lin; Hsin-Hua Chen (PLoS ONE)
Common variable immunodeficiency (CVID) is one of the primary immunodeficiency diseases that occur in both children and adults. We present here a nationwide, population-based epidemiological study of CVID across all ages in Taiwan during 2002-2011. Using the International Classification of Diseases, Ninth Revision code 279.06, cases of CVID were identified from Taiwan's National Health Insurance Research Database from January 2002 to December 2011. Age- and sex-specific incidence and prevalence rates were calculated. A total of 47 new cases of CVID during 2002-2011 were identified. Total prevalence rose from 0.13 per 100,000 in 2002 to 0.28 per 100,000 in 2011. The annual incidence rate during 2002-2011 was 0.019 per 100,000. Cases were equally distributed between males and females and males mostly occurred in younger patients. This nationwide population-based study showed that the incidence and prevalence of CVID in Taiwan were lower than that in Western countries.